Antiseptic effect of antimicrobial peptide psacotheasin 2 derived from the yellow-spotted longicorn beetle (Psacothea hilaris). (October 2021) - Shin, Yong Pyo; Lee, Joon Ha; Choi, Ra-Yeong; Lee, Hwa Jeong; Baek, Minhee; Kim, In-Woo; Seo, Minchul; Kim, Mi-Ae; Kim, Seong Hyun; Hwang, Jae Sam
Abstract: Given the challenges posed by antibiotic resistant microbes and the high mortality rate associated with sepsis, there is an urgent need to develop novel peptide antibiotics that exhibit both antimicrobial and anti-inflammatory activities. Herein, we evaluated antimicrobial activity and anti-inflammatory activity of psacotheasin 2, one of the antimicrobial peptide candidates identified previously using an in silico analysis on the transcriptome of Psacothea hilaris . In addition to exhibiting antimicrobial activities against microorganisms without inducing hemolysis, psacotheasin 2 also decreased the nitric oxide production in lipopolysaccharide (LPS)-induced Raw264.7 cells. Moreover, ELISA and western blot analysis revealed that psacotheasin 2 reduced the expression levels of pro-inflammatory enzymes such as inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). Further, we found that psacotheasin 2 markedly reduced the expression levels of pro-inflammatory cytokines (IL-6 and IL-1β) by regulating mitogen-activated protein kinases (MAPKs) and nuclear factor-kB (NF-kB) signaling in LPS-induced Raw264.7 cells. We also confirmed that the binding of psacotheasin 2 to bacterial cell membranes occurs via a specific interaction with LPS. In mouse models of LPS-induced shock, psacotheasin 2 significantly enhanced the survival rate and recovered weight by attenuating pro-inflammatory cytokines. Thus, psacotheasin 2 could be a promising candidate as a peptide antiseptic agent. Graphical abstract: Image 1 Highlights: Psacotheasin 2 is a potent antimicrobial peptide with anti-inflammatory activities. It binds to and neutralizes LPS in a dose-dependent manner. It alleviates LPS-induced inflammation by suppressing TNF-a, IL-6, and IL-1β levels. Its anti-inflammatory activity is mediated by MAPK and NF-kB signaling pathways.